Application of Local Bacillus Thuringiensis Isolates as Biopesticides for Control of Spodoptera Frugiperda in Maize - Salaki, Christina Leta; Makal, Henny V.; Paat, Frangky J.; Pamandungan, Yefta (Sam Ratulangi University, 2026)
The fall armyworm, Spodoptera frugiperda, is an invasive pest that threatens maize production and can increase dependence on synthetic insecticides, highlighting the need for locally effective biological control options. This study screened 24 local Bacillus thuringiensis isolates for insecticidal activity against third instar S. frugiperda using a maize leaf dip feeding bioassay. For initial screening, maize leaf sections were treated with 1.5 × 10⁷ spores mL⁻¹ and offered to larvae (30 larvae per isolate), with mortality recorded up to 72 h. Isolates producing at least 50 percent mortality at 72 h were advanced to pathogenicity testing. Selected isolates were evaluated at five concentrations (1.5 × 10³ to 1.5 × 10⁷ spores mL⁻¹) to estimate LC50 at 72 h, and at 1.5 × 10⁷ spores mL⁻¹ to estimate LT50; parameters were calculated by probit analysis and reported with 95 percent fiducial limits. Ten isolates met the screening criterion, and isolate ITH produced the highest mortality (93.3 percent) at 72 h. ITH also showed the greatest pathogenicity, with an LC50 of 7.5 × 10³ spores mL⁻¹ and an LT50 of 19.5 h, indicating high potency and rapid action relative to other candidates. The results demonstrate substantial variability among local Bt isolates and identify promising strains for further development. Future work should confirm isolate identity, characterize toxin profiles, optimize production and formulation, and validate efficacy and crop protection performance under semi field and field conditions for integration into maize integrated pest management. Keywords: Bacillus thuringiensis; biopesticide; fall armyworm; leaf dip bioassay; maize; Spodoptera frugiperda